Investigating the Relationship between Attention Deficit Hyperactivity Disorder and Drug Abuse: a Case-Control Study - Noyani 1, Amir; Chaman 2, Reza; Mousavi 3, Seyed Abbas; Khorsand 4*, Mohammadreza (Shahroud Journal of Medical Sciences, 2019)
Background: Hyperactivity disorder is one of the most common psychiatric disorders that can lead to negative consequences such as addiction in adolescence. The purpose of this study was to determine the relationship between addiction and hyperactivity disorder in Shahroud city. Methods: This is a case-control study with sample size 240. The case group included methadone-treated addicted drug users and the control group including patients admitted to the surgical wards of Imam HosseinShahroud Hospital who have no addiction to any drugs.We used the Conges(CAAR-S: OV) short-acting diagnostic questionnaire ofadolesent (CAARS) for collectting information. For analysisng the data SPSS version 21 was used and significant level was considered (0.05).Results: This study included 150 controls and 90 cases. The age avrege of cases and controls was 36.97 ± 10.40 and 31.57 ± 10.46 years, respectively. Although case and control were statistically different in restlessness-hyperactivity(P = 0.034), they do not statistically differ in the presence of Hyperactivity Disorder (P = 0.911).Conclutions:Since in the present study, only the subgroup of restlessness-hyperactivity in the two groups was significantly different (the value was greater for the control group), it can be argued that the modesty of addicted persons is partially reduced by opiate.